НЕЛИНЕЙНАЯ ЭЛЕКТРИЧЕСКАЯ МОДЕЛЬ ПРОВОДИМОСТИ БИОЛОГИЧЕСКОЙ КЛЕТКИ - Шигимага, В.А. (Інститут електродинаміки НАН України, Київ, 2013)
The model of biological cell conductivity as equivalent nonlinear electric scheme is represented. A model assumes that structural elements of cell are a membrane and cytoplasm, can be represented as a resistor-capacity circuit, the calculation of which can be executed by known rules for electric elements and connections. Equation of nonlinear function of single cell conductivity is got, and on this basis and conductivity of 2-cell embryo, depending on the external voltage put by means of microelectrodes on the method of pulse conductometry. It is shown that for 2-cell embryo additionally there is dependence of conductivity on cell orientation in relation to the microelectrodes axis. The built electric model adequately explains the experiments on measuring of cells conductivity in pulse electric field. References 9, figures 5.